Gomphus floccosus (Schw.) Sing. extract attenuates alcoholic liver disease by suppressing macrophage glycolysis and M1 polarization - Ruan, Tianyin; Li, Xutao; Li, Mingyue; Wang, Siyuan; Shen, Li; Liu, Chenghai; Peng, Yuan; Tao, Yanyan (Frontiers in Immunology, 2026)
BackgroundAlcoholic liver disease (ALD) remains a leading cause of global mortality, yet the development of safe and effective multi-target therapies continues to be a significant challenge. Macrophage-mediated inflammation plays a pivotal role in the pathogenesis of ALD, with macrophage glycolysis reprogramming emerging as a critical immunometabolic checkpoint that drives disease progression. Gomphus floccosus (Schw.) Sing (Gf), a mushroom traditionally employed in southwestern China for the treatment of hepatobiliary disorders, holds therapeutic potential. However, its clinical application is limited by gastrointestinal side effects, and its active components and underlying mechanisms in ALD remain largely unexplored. This study aims to determine whether a standardized extract of Gf alleviates ALD by specifically modulating the macrophage glycolysis-M1 polarization axis.MethodsUltra-high-performance liquid chromatography-mass spectrometry (UHPLC-MS) was utilized to characterize the chemical profile of the Gf extract. An in vivo ALD mouse model was established using the Lieber-DeCarli ethanol diet with two distinct administration routes. In vitro studies were conducted using lipopolysaccharide (LPS)/ethanol-stimulated macrophages (RAW264.7 and THP-1 cell lines). Comprehensive analyses, including transcriptomic sequencing, pathway enrichment studies, and validation through immunohistochemistry, immunofluorescence, qRT-PCR, Western blotting, and metabolic flux analysis, were performed to elucidate the underlying mechanisms.ResultsThree major constituents were identified in the Gf extract. Treatment with Gf extract significantly mitigated ALD pathology, as evidenced by reductions in steatosis, oxidative stress, and inflammation. Transcriptomic analysis identified 231 differentially expressed genes, with significant enrichment in the glycolysis pathway. Mechanistically, the Gf extract suppressed key glycolytic enzymes, including GLUT1, GCK, HK2, PKM2, and LDHA, as well as lactate production in macrophages. This inhibition effectively reduced pro-inflammatory cytokine secretion, chemotaxis, and M1 polarization.ConclusionThe hepatoprotective effects of Gf extract against ALD are mediated through the suppression of macrophage glycolytic reprogramming and M1 polarization, providing an immunological basis for its traditional use in hepatobiliary disorders.